2013
DOI: 10.1371/journal.pone.0058823
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Molecular Analysis of Sentinel Lymph Node May Be Predictive of Axillary Node Status in Breast Cancer Classified by Molecular Subtypes

Abstract: To determine the performance of intraoperative one-step nucleic acid amplification (OSNA) assay in detecting sentinel lymph node metastases compared to postoperative histology taking into account breast cancer molecular classification and to evaluate whether the level of cytokeratin 19 mRNA copy number may be useful in predicting the likelihood of a positive axillary lymph node dissection. OSNA assay was performed in a prospective series of 903 consecutive sentinel lymph nodes from 709 breast cancer patients u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 34 publications
(38 reference statements)
2
17
1
2
Order By: Relevance
“…These findings were in accordance with previous reports [7][8][9][10][11][12][13]. Our study could not find out the association between molecular subtype and SLN metastasis, in contrast with previous reports [3,6,[14][15][16][17][18][19][20][21][22]. Possible explanation to the discrepancy between previous reports and our results is that the distribution in among subtype might affect the results: HER 2 type was very few (7.0%), and this seems to be the reason why low frequency of SLN metastasis in HER 2 subtype was shown in our study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These findings were in accordance with previous reports [7][8][9][10][11][12][13]. Our study could not find out the association between molecular subtype and SLN metastasis, in contrast with previous reports [3,6,[14][15][16][17][18][19][20][21][22]. Possible explanation to the discrepancy between previous reports and our results is that the distribution in among subtype might affect the results: HER 2 type was very few (7.0%), and this seems to be the reason why low frequency of SLN metastasis in HER 2 subtype was shown in our study.…”
Section: Discussionsupporting
confidence: 86%
“…A various clinicopathological factors have been identified as independent predictors of axillary lymph node metastasis in early stage breast cancer [6]. These include clinical palpability [7][8][9][10], tumor size [7][8][9][10][11][12][13], lymphatic or vascular involvement [7][8][9][10][11]13], tumor grade [7,10], hormone receptor (HR) status [12,13], age [8,11,12], and molecular subtypes [3,6,[14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Among these, the study of Buglioni et al 22 demonstrated that a specific cut-off of 2000 CK19 mRNA copy numbers in the SLN could predict the likelihood of finding positive ALN, identifying patients who are eligible for ALND. This copy number was obtained from the molecular analysis of only a part of the SLN: indeed, this cut-off was based on a 4-slice model and only half of the SLN was used for OSNA.…”
Section: Introductionmentioning
confidence: 99%
“…A pesar de estar bien establecidas las diferencias pronósticas entre los distintos PM, son muy escasos los estudios que lo aplican en la evaluación de riesgo de axila metastásica 21,35 . Buglioni et al demuestran, incluyendo el PM en el estudio multivariante, que los subtipos agresivos como el HER2, se asocian a mayor porcentaje de metástasis axilares 20 .…”
Section: Discussionunclassified
“…Por otra parte, se ha descrito que la tasa de metástasis axilares no centinelas varía en relación al inmunofenotipo tumoral (PM) 19,20 .…”
Section: Introductionunclassified